2014
DOI: 10.11622/smedj.2014020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and its associated risk factors among Chinese adults in a Malaysian suburban village

Abstract: MeThODs This was a cross-sectional study conducted among the Chinese residents in Seri Kembangan New Village, Klang Valley, Selangor, Malaysia. Convenience sampling was used for the selection of participants. Body weight, height, waist and hip circumferences, and blood pressure were measured. Fasting venous plasma was drawn for the measurement of fasting glucose level and lipid profile. Data on sociodemographic factors, dietary habits, physical activity, perceived stress level and sleep duration were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…In another study among 4,341 Malaysian adults, the findings noted that the prevalence of impaired fasting glucose (elevated FBG) rose along with BMI (Nazaimoon et al, 2011). In addition, obese adults were found to have higher TG levels than nonobese adults, as reported in a study of 258 Chinese Malaysian obese adults from urban communities (Chew et al, 2014). Based on the previous findings, an association is identified between obesity and elevated BP, FBG, and TG level.…”
Section: Introductionsupporting
confidence: 52%
“…In another study among 4,341 Malaysian adults, the findings noted that the prevalence of impaired fasting glucose (elevated FBG) rose along with BMI (Nazaimoon et al, 2011). In addition, obese adults were found to have higher TG levels than nonobese adults, as reported in a study of 258 Chinese Malaysian obese adults from urban communities (Chew et al, 2014). Based on the previous findings, an association is identified between obesity and elevated BP, FBG, and TG level.…”
Section: Introductionsupporting
confidence: 52%
“…The present review suggests that protein intake of Malaysian adults, especially older adults, either met or exceeded national recommendations, and that animal rather than vegetable protein was the main source. Findings from cross-sectional studies showed that a “meat, rice, and noodles” diet among Chinese Malaysians was associated with higher BMI, blood glucose, and lipids, with certain alleles further increasing the risk from this dietary pattern [ 35 ], and that soy milk consumption reduced risk of obesity [ 36 ]. Case–control studies among Malaysian cancer patients suggested that red meat intake was associated with increased risk of colorectal adenoma (CRA) (OR 2.51, 95% CI 1.02, 6.28) [ 37 ] and prostate cancer (OR 12.23, 95% CI 3.89, 39.01) [ 38 ], while soybean and soy products reduced the risk of CRA (OR 0.38, 95% CI 0.15, 0.98) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Case–control studies among Malaysians showed that fruits and vegetables, particularly tomatoes, were associated with reduced risk of prostate cancer [ 20 , 38 ] and colorectal adenoma [ 37 ], while a higher healthy eating index score and antioxidants associated with fruit and vegetable intake reduced risk of breast cancer [ 61 , 62 ]. Among Chinese Malaysian adults [ 36 ], a perception that “a balanced diet consisted mainly of vegetables” was associated with reduced risk of obesity. Malaysian women with low fiber intake (<10 g/day) had a 2.2 times higher risk of developing breast cancer [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Th e dramatic increase in the prevalence of obesity has been reported to be associated with the increase in the prevalence of chronic diseases. Th e excessive fat deposition in obese individuals has been established to be correlated with the development of metabolic and cardiovascular complications (Chew et al 2014). Th e health consequences associated with obesity diff er depending on the place where the adipose tissue is stored; for instance, subcutaneously versus internally (visceral) (Pou et al 2007;Ducluzeau et al 2010;Wildman et al 2011).…”
mentioning
confidence: 99%